The last song - Sparks, Nicholas (London : Sphere, 2014)
Seventeen-year-old Ronnie Miller is resentful when her mother insists she and her ten-year-old brother spend the summer with their estranged father in North Carolina, and while things get off to a rocky start, Ronnie eventually makes friends and begins to better understand her dad and why he wanted her to visit. Includes a reading group guide.
"Now a major motion picture"--Cover.
Adult.
Adult
Keywords: Teenage girls -- Fiction; Bildungsromans; Girls -- Fiction; Love stories; Movie novels; Teenagers -- Fiction; Bildungsromans; Love stories; Movie novels